Agronomical screening of OGLE1040/TAM O-301 oat genetic mapping population - Dumlupinar, Ziya; Güngör, Hüseyin; Dokuyucu, Tevrican; Herek, Sevgi; Tekin, Ali; Akkaya, Aydin (Penerbit Universiti Kebangsaan Malaysia, 2019)
In recent years, mapping populations have provided improvements for oat genomic researches. A two-year study was conducted in East-Mediterranean conditions using Ogle1040/TAM O-301 pure-line mapping population including 136 individuals and parents. Stem diameter (SD), plant height (PH), panicle length (PL), vegetative period (VP), grain filling period (GFP), days to maturity (DM), grain number per panicle (GNP), grain weight per panicle (GWP), thousand kernel weight (TKW) and grain yield (GY) were investigated in 2014 and 2015 cropping seasons in Kahramanmaras. All the investigated traits were significantly different for years (p<0.01) and genotypes (p<0.05 and p<0.01) except SD and GNP. Genotype x year (G x Y) interaction was significant for PL, VP, GFP, DM and GY (p<0.01). In the first year, the average GY per row was 227.6 g, whilst it was 184.5 g in the second year. In terms of GY, the parents Ogle 1040 and TAM O-301 showed lower performance (154.5 and 111.5 g/row, respectively) compared to Ogle1040/TAM O-301 (OT) population average (206 g/row). OT129 genotype had the highest GY with 360 g/row. Principal component (PC) factor analysis yielded 10 PC explaining 100% of total variance in the data and the chi-square values of the PC1 to PC9 were found significant. According to PC biplot analysis, genotypes with high GY, TKW, GNP, GWP, PL and GFP were located throughout the right quadrants whereas the genotypes with high VP, DM and SD were located throughout the left quadrants. The relationships between PH × GY, GWP × GNP and GWP × TKW were positive and significant.